HIGH FOOD PRICES: The What, Who and How of Proposed Policy Actions - von Braun, Joachim; Rosegrant, Mark W.; Torero, Máximo; Hoddinott, John (2009)
Joachim von Braun, Mark W. Rosegrant, Maximo Torero, John Hoddinott 28th May 2008, International Food Policy Research Institute, Washington D.C.